2008
DOI: 10.1159/000161565
|View full text |Cite
|
Sign up to set email alerts
|

Esophagectomy in Scleroderma: Report of a Case

Abstract: Scleroderma is a generalized autoimmune disease with variable involvement of the skin and major organs (esophagus, lung, heart and kidney). Scleroderma is essentially a skin disease that frequently involves the digestive system. In scleroderma, the esophagus is the most frequently affected organ of the digestive system, and esophageal dysmotility, reflux and stricture may be observed in the advanced stage. Balloon dilatation and bougienage are generally sufficient in patients developing stricture, and the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…One of them is esophageal stricture, which finally leads to disordered motility with contraction amplitudes or loss of peristalsis. These end-stage abnormalities result from a variety of esophageal diseases, such as caustic injury (2,3), chronic reflux disease (4), achalasia (5), giant mass in the esophagus (6), or scleroderma of connective tissue disease (7).…”
Section: Factors Leading To Esophageal Failure In Benign Diseasementioning
confidence: 99%
“…One of them is esophageal stricture, which finally leads to disordered motility with contraction amplitudes or loss of peristalsis. These end-stage abnormalities result from a variety of esophageal diseases, such as caustic injury (2,3), chronic reflux disease (4), achalasia (5), giant mass in the esophagus (6), or scleroderma of connective tissue disease (7).…”
Section: Factors Leading To Esophageal Failure In Benign Diseasementioning
confidence: 99%
“…In this study, we provided the rst evidence that BLM caused gastrointestinal brosis, demonstrated both histologically and functionally. The gastrointestinal lesions of SSc patients included esophageal dysmotility, lower esophageal sphincter insu ciency, gastroesophageal re ux, esophageal stricture, a reduction in motility in the intestine, wide-mouthed diverticula in the large intestine and rectal atonia in advanced cases [15]. BLM-induced gastrointestinal lesions resembled several patterns of gastrointestinal lesions observed in SSc patients.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, we provided the first evidence that BLM caused gastrointestinal hyperproliferative and prefibrotic response, demonstrated both histologically and functionally. The gastrointestinal lesions of SSc patients included esophageal dysmotility, lower esophageal sphincter insufficiency, gastroesophageal reflux, esophageal stricture, a reduction in motility in the intestine, wide-mouthed diverticula in the large intestine, and rectal atonia in advanced cases [17]. BLM-induced gastrointestinal lesions resembled several patterns of gastrointestinal lesions observed in SSc patients.…”
Section: Discussionmentioning
confidence: 76%